The interplay between kisspeptin and endocannabinoid systems modulates male hypothalamic and gonadic control of reproduction in vivo - Marino, Marianna; D’Auria, Raffaella; Mele, Elena; Pastorino, Grazia Maria Giovanna; Di Pietro, Paola; D’Angelo, Stefania; Della Rocca, Natalia; Operto, Francesca Felicia; Vecchione, Carmine; Fasano, Silvia; Pierantoni, Riccardo; Viggiano, Andrea; et al. (Frontiers in Endocrinology, 2023)
Introduction: Male reproduction is under the control of the hypothalamus-pituitary-gonadal (HPG) axis. The endocannabinoid system (ECS) and the kisspeptin system (KS) are two major signaling systems in the central and peripheral control of reproduction, but their possible interaction has been poorly investigated in mammals. This manuscript analyzes their possible reciprocal modulation in the control of HPG axis.Materials and methods: Adolescent male rats were treated with Kisspeptin-10 (Kp10), and the endocannabinoid anandamide (AEA), the latter alone or in combination with the type 1 cannabinoid receptor (CB1) antagonist rimonabant (SR141716A). Hypothalamic KS system and GnRH expression, circulating sex steroids and Kisspeptin (Kiss1) levels, and intratesticular KS and ECS were evaluated by immunohistochemical and molecular methods. Non-coding RNAs (i.e., miR145-5p, miR-132-3p, let7a-5p, let7b-5p) were also considered.Results: Circulating hormonal values were not significantly affected by Kp-10 or AEA; in the hypothalamus Kp10 significantly increased GnRH mRNA, aromatase Cyp19, Kiss1 and Kiss1 receptor (Kiss1R) proteins. By contrast, AEA treatment affected the hypothalamic KS at protein levels, with opposite effects on ligand and receptor, and SR141716A was capable to attenuate AEA effects. Among the considered non-coding RNA, only the expression of miR145-5p was positively affected by AEA but not by Kp-10 treatment. Localization of Kiss1+/Kiss1R+ neurons in the arcuate nucleus, revealed an increase of Kiss1R-expressing neurons in Kp-10 and AEA treated animals associated to enlargement of the lateral ventricles in Kp-10 treated animals. In brain and testis, the selected non-coding RNA resulted differently modulated by Kp-10 or AEA. Lastly, in the testis, AEA treatment affected the KS at protein levels whereas Kp-10 affected the intragonadal levels of CB1 and FAAH, the main modulator of AEA tone. Changes in pubertal transition-related miRNAs and the intratesticular distribution of Kiss1, Kiss1R, CB1 and CB2 following KP and AEA treatment corroborate the KS-ECS cross talk also showing that CB1 receptor is involved in this interplay.For the first time in mammals, we report the modulation of the KS in both hypothalamus and testis by AEA and revealed the KP-dependent modulation of CB1 and FAAH in the testis. KP involvement in the progression of spermatogenesis is also suggested.